Business Judgment Rule and Corporate Criminal Liability in Indonesian SOEs: Distinguishing Business Risk from State Loss - Serlika Aprita; Khalisah Hayatuddin (UIN Sunan Gunung Djati, 2026)
This study examines the application of the Business Judgment Rule (BJR) to the responsibilities of directors of State-Owned Enterprises (SOEs), emphasizing that directors hold a strategic position as a corporate organ fully responsible for company management, as stipulated in the SOE Law and the Limited Liability Company Law. Using a normative juridical research method with a legislative approach, a conceptual approach, and a literature review, this study analyzes the extent to which the BJR doctrine can provide legal protection for directors when their business decisions result in losses or are deemed detrimental to state finances. The results indicate that the BJR is an important instrument to ensure that directors are not automatically held accountable as long as business decisions are made in good faith, prudently, do not exceed their authority, and are based on adequate information. This study also found that the different characteristics of SOEs as business entities and as public mandate holders often cause the application of the BJR to conflict with the paradigm of state losses, thus creating legal uncertainty for directors. Therefore, consistent implementation of the BJR is necessary to provide proportional legal protection and encourage SOE directors to carry out their business functions professionally without fear of criminalization of decision-making.